Reliability and validity of sprint performance using the Alex7 motorized device - Austra Skujytė; Inga Lukonaitienė; Inga Lukonaitienė; Jūratė Stanislovaitienė; Viktoras Šilinskas; Kristina Bradauskienė; Gediminas Mamkus; Gediminas Mamkus; Sigitas Kamandulis; Sigitas Kamandulis (Frontiers Media S.A., 2024)
IntroductionAdvancements in technology have recently made it possible to implement effective training solutions across different environmental conditions. This study evaluated the reliability and validity of measures obtained from the innovative motorized device, Alex7 (Inosportas, Lithuania), and differences in speed and kinematic characteristics between resisted and assisted sprinting in young football players.MethodsTwenty-seven male athletes (mean age: 16.5 ± 0.8 years; height: 179.5 ± 6.9 cm; body weight: 67.7 ± 8.3 kg) each performed 30-m sprints twice under three different conditions: regular, resisted, and assisted sprinting. The Alex7 device provided the assistance and resistance during sprints. Results were compared with those from Witty timing gates. Ground contact time, flight time, stride length, and pace were measured using the OptoJump system. Reliability was assessed using two-way mixed intraclass correlation coefficients (ICCs) for single measures, the standard error of the mean (SEM), and the coefficient of variation (CV). Pearson's correlation coefficient determined the associations between Alex7 and Witty timing systems. Criterion-referenced validity was based on the mean difference and CV. Systematic bias was determined by limits of agreement using Bland-Altman analysis.ResultsRunning times obtained using the Alex7 equipment exhibited good to excellent test-retest reliability between sessions (ICC, 0.83-0.94) and good to excellent correlation (Pearson's r = 0.88-0.98) between the Alex7 and Witty systems in both assisted and resisted running conditions. However, the Alex7 device consistently produced longer running times than the Witty device (up to 0.16 s difference, p < 0.001). The different running conditions produced substantial variations in kinematic variables, such as stride length, ground contact time, and running speed (p < 0.001 for all), but the effects on flight time and running pace were smaller.DiscussionThe Alex7 device shows high reliability for creating resisted and assisted running conditions for young football players. However, it tends to overestimate running time, necessitating caution when assessing the time parameters.